Schools in the City of Buenos Aires: scenes of language policies - Varela, Lía; Verdelli, Ana (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This article focuses on certain language policies that have taken place in the schools of the City of Buenos Aires. More specifically, from a historical-structural perspective (Tollefson, 2015) and within the theory of language management (Spolsky, 2004, 2009), this article inquires into the socio-historical factors that determine the presence or absence of the foreign languages taught at primary level schools as well as their geographical distribution. In this way, we expect to contribute to a deeper understanding of the emergence, validity and transformational capacity of the language policies in the school domain.